2011
DOI: 10.1055/s-0030-1270968
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Phenolic Constituents and Medicinal Activities of Northern Labrador Tea,Rhododendron tomentosumssp.subarcticum, an Inuit and Cree First Nations Traditional Medicine

Abstract: Northern Labrador tea, Rhododendron tomentosum ssp. subarcticum, is one of the most commonly used medicinal plants by Inuit and other First Nations peoples of Canada. The phenolic profile and seasonal variation of this commonly used medicinal plant remains largely unknown. To assess optimal harvesting time, R. tomentosum was collected in accordance with traditional knowledge practices bimonthly throughout the snow-free summer in Iqaluit, Nunavut. The antioxidant potency was measured in a DPPH radical scavengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 31 publications
(33 reference statements)
0
51
0
1
Order By: Relevance
“…Ferrier et al (2012) showed relationships between total phenolics and glycation end-product inhibition within the Vaccinium genus, which varied with latitude. As well, McIntyre et al (2008) and Black et al (2011) reported variations in pharmacological activities associated with seasonal variations in the phenolic concentrations of plants from Ericaceae, V. angustifolium and R. tomentosum, respectively. Although biologically active constituents in R. groenlandicum were found to vary geographically, pharmacological bioassays need to be performed to properly assess the pharmacological significance of these observations.…”
Section: Environmental and Climatic Relationshipsmentioning
confidence: 91%
See 2 more Smart Citations
“…Ferrier et al (2012) showed relationships between total phenolics and glycation end-product inhibition within the Vaccinium genus, which varied with latitude. As well, McIntyre et al (2008) and Black et al (2011) reported variations in pharmacological activities associated with seasonal variations in the phenolic concentrations of plants from Ericaceae, V. angustifolium and R. tomentosum, respectively. Although biologically active constituents in R. groenlandicum were found to vary geographically, pharmacological bioassays need to be performed to properly assess the pharmacological significance of these observations.…”
Section: Environmental and Climatic Relationshipsmentioning
confidence: 91%
“…ex Bigelow, Kalmia angustifolia L., Rhododendron tomentosum Harmaja, Vaccinium vitis-idaea L., and Vaccinium angustifolium Aiton (Harris et al 2007;McIntyre et al 2008;Saleem et al 2010;Black et al 2011;Ferrier et al 2012). These species also appear in the CEI pharmacopoeia and, like R. groenlandicum, have been screened by the CIHR Team in Antidiabetic Aboriginal Medicines and shown to possess antioxidant activity and antidiabetic potential (Spoor et al 2006;McIntyre et al 2008;Harbilas et al 2009;Black et al 2011;Ferrier et al 2012). More specifically, three of these compounds, (+)-catechin, (-)-epicatechin, and quercetin, have been found responsible for the adipogenic activity of R. groenlandicum in bioassay-guided fractionation (Ouchfoun 2011).…”
Section: Phenolic Content and Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal variations in natural compounds are fairly common and can contribute to variations of the finished products (Chou et al, 2009). Black et al (2011 reported that there were significant seasonal variations in fifteen constituents of Northern Labrador Tea (Rhododendron tomentosum ssp.…”
Section: Compoundsmentioning
confidence: 99%
“…In this study, the content of isoquercitrin was 0.23 mg/g in HHF provenance, and it was much lower than the report from Fang et al (2011), likely caused by seedling ages and extraction methods. Therefore, JXS is selected to be the optimal provenance based on the quantification of seven bioactive compounds.Seasonal variations in natural compounds are fairly common and can contribute to variations of the finished products (Chou et al, 2009). Black et al (2011 reported that there were significant seasonal variations in fifteen constituents of Northern Labrador Tea (Rhododendron tomentosum ssp.…”
mentioning
confidence: 99%